Dilemmas concerning the canon law (I) – ordinatio rationis or dei in the light of Encyclical Fides et ratio - GAŁKOWSKI, TOMASZ (Prawo Kanoniczne, 2017)
The content of the study are dilemmas connected with the denition of the act proposed by St. omas Acquinas. e attention was focused on its rst element, which is ordinatio. Acknowledging the denition of the canon law understood as ordination dei does not equal the passive role of reason in accepting it, since the act of faith remains the act of human reason, whose object is the truth accepted as such by virtue of God`s authority. e role of reason does not come down only to historical perception and shaping the demands of God`s law. e canon law, which is merely a human, legally binding way of passing on faith, is the token of this act, through which one accepts what was revealed by God and then expresses in norms as the truth. Ordinatio dei nds its place in the norm of faith (des qua) and its acceptance (des quae) and ordination rationis in the process of expressing it by means of a tool which is a normative act in the form of legal regulation.